2020
DOI: 10.1080/02626667.2019.1709641
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three types of laser optical disdrometers under natural rainfall conditions

Abstract: Optical disdrometers can be used to estimate rainfall erosivity; however, the relative accuracy of different disdrometers is unclear. This study compared three types of optical laser-based disdrometers to quantify differences in measured rainfall characteristics and to develop correction factors for kinetic energy (KE). Two identical PWS100 (Campbell Scientific), one Laser Precipitation Monitor (Thies Clima) and a firstgeneration Parsivel (OTT) were collocated with a weighing rain gauge (OTT Pluvio 2) at a sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 35 publications
5
46
0
4
Order By: Relevance
“…However, despite their spatial separation, both Parsivel disdrometers showed similar distributions with an overestimation of the velocity of the majority of drops (up to around a diameter of 1 mm) compared to the terminal velocity line. This distribution was also observed in other studies [41,43,60].…”
Section: Drop Size and Velocity Distributionssupporting
confidence: 89%
See 4 more Smart Citations
“…However, despite their spatial separation, both Parsivel disdrometers showed similar distributions with an overestimation of the velocity of the majority of drops (up to around a diameter of 1 mm) compared to the terminal velocity line. This distribution was also observed in other studies [41,43,60].…”
Section: Drop Size and Velocity Distributionssupporting
confidence: 89%
“…It may also suggest that rainfall intensity measurement between the PWS PE and the rain gauge may deviate more within events than can be seen from the daily comparison. This was shown by Johannsen et al [43], who found that the rain gauge often measured higher intensities than four collocated disdrometers at the minute-scale.…”
Section: Validation Of Site-specific Rainfall Kinetic Energy-intensitmentioning
confidence: 69%
See 3 more Smart Citations